2014
DOI: 10.1590/1984-70332014v14n4n41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of popcorn families using a Bayesian approach via the independence chain algorithm

Abstract: -The objective of this study was to examine genetic parameters of popping expansion and grain yield in a trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…In the present study, the heritability calculated on a family-mean basis through the four cycles was 0.49, 0.37, and 0.36 for plant height, grain yield, and popping expansion, respectively. These results are in agreement with those found by Rodovalho et al (2014) in a trial of half-sib families of popcorn evaluated using a Bayesian approach; family-mean heritability estimates ranged from 0.22 to 0.44, and from 0.28 and 0.49, for popping expansion volume and grain yield, respectively. On the other hand, Arnhold et al (2009) found larger estimates of heritability in Brazil suggesting good potential for improving popping expansion volume by selection and breeding; single-site heritability for popping expansion in S3 families ranged from 0.58 to 0.85 with a mean of 0.7.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the heritability calculated on a family-mean basis through the four cycles was 0.49, 0.37, and 0.36 for plant height, grain yield, and popping expansion, respectively. These results are in agreement with those found by Rodovalho et al (2014) in a trial of half-sib families of popcorn evaluated using a Bayesian approach; family-mean heritability estimates ranged from 0.22 to 0.44, and from 0.28 and 0.49, for popping expansion volume and grain yield, respectively. On the other hand, Arnhold et al (2009) found larger estimates of heritability in Brazil suggesting good potential for improving popping expansion volume by selection and breeding; single-site heritability for popping expansion in S3 families ranged from 0.58 to 0.85 with a mean of 0.7.…”
Section: Resultssupporting
confidence: 90%
“…Marginal posterior distributions of the variance components, genotypic values, CVG, and family-mean heritabilities, were obtained using the Independence Chain algorithm from the MIXED procedure of SAS, with the option PRIOR and posterior sample size of 5000. The prior densities of the variance components were obtained in the first run using Jeffreys' prior distribution; and subsequently, the second run was performed using these densities -DATA statement (Rodovalho et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important detail that possibly hampers to choose the most suitable tester is the fact that the two main traits of the crop, popping expansion and grain yield, which should be evaluated together, have different mechanisms of inheritance (Pereira and Amaral Júnior 2001). Popping expansion is controlled by a small number of genes and there is predominance of additive gene action (Yongbin et al 2012;Rodovalho et al 2014). On the other hand, grain yield is genetically controlled by a large number of genes with predominance of non-additive gene effects.…”
Section: Introductionmentioning
confidence: 99%
“…A credible interval (or in general, a credible set) is the Bayesian analogue of a confidence interval. One advantage of the Bayesian procedures is the possibility of using the confidence limits (or credibility regions in the Bayesian context) as an alternative estimation of genetic parameters (Rodovalho et al, 2014). Agresti and Min (2005) discussed Bayesian confidence intervals for association parameters.…”
Section: (X)mentioning
confidence: 99%